Survey on data transmission in Bluetooth technology - Zhi-hong QIAN; Dan LIU (Tongxin xuebao)
The different impact assessments on performance of data transmission of multiple Bluetooth protocol versions were analyzed.Packet selection algorithms,retransmission mechanisms,interference and security were discussed respectively.Strategies,employing extended-golay code and minimum frequency shift keying (MSK) modulation were proposed,which enhanced the probability of anti-interference and throughput of data packet.Moreover,a co-channel interference suppression approach based on channel switching and MSK modulation was proposed,which improved the carrier to interference ratio and throughput in piconets.Finally,the work was summarized and expectations as well as premeditation of the future were presented.